Avoidant Restrictive Food Intake Disorder: A Narrative Review of Types and Characteristics of Therapeutic Interventions - Marcella Di Cara; Chiara Rizzo; Francesco Corallo; Davide Cardile; Rocco Salvatore Calabrò; Angelo Quartarone; Martina Buda; Francesca Cucinotta (MDPI AG, 2023)
The diagnosis of avoidant/restrictive food intake disorder (ARFID) was added to the diagnostic and statistical manual of mental disorders (DSM-5) just 10 years ago. This disorder consists of the failure to meet one's nutritional and/or energy needs, which may result in significant weight loss, significant nutritional deficit or functioning dependent on enteral nutrition or oral supplements. In children with this disorder, development is often problematic, and there is also marked interference with psychosocial functioning at all ages. The causes leading to food avoidance in these patients may be related to a lack of interest, to the sensory properties of the food or to the possible adverse consequences associated with it. Given the multitude of aspects involved in this disorder and the impact it has especially on younger patients, more and more studies are addressing treatments and related benefits and/or complications. A narrative review of currently published studies was performed for articles published before 5 March 2023 on therapeutic interventions in patients with ARFID. Because of the large number of results obtained, this review was conducted only via PubMed in order to analyze and discuss children and adolescent ARFID treatments reported in literature. The treatments most often referred to in the literature are cognitive behavioral therapy, family-based therapy and pharmacological treatment. All the data on these treatments are promising. However, due to the recent introduction of this disorder and the limited data still available, a multidisciplinary approach seems to be the best option.